2022
DOI: 10.47836/mjmhs.18.s15.14
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Challenges of an Outsource Hospital Foodservice Operation: A Narrative Thematic Analysis

Abstract: Introduction: Hospital foodservice is one of the key performance metrics that should be constantly monitored to maintain and improve the quality of hospital services. However, hospital foodservice must overcome obstacles and constraints that can impact the quality of services supplied. This study explored the barriers and challenges foodservice employees encountered during food production and serving meals to patients. Methods: A qualitative study was conducted with thirteen foodservice employees (N = 13) at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The study conducted by Chik et al [1] has highlighted that plate waste generation, a type of food waste, is significantly influenced by temperature and taste. These findings align with another study by Osman et al [2], which revealed patient dissatisfaction with the taste of hospital food. According to the staff, it is because salt usage can be little to none and sometimes not used, depending on the prescribed diet.…”
Section: Introductionsupporting
confidence: 92%
“…The study conducted by Chik et al [1] has highlighted that plate waste generation, a type of food waste, is significantly influenced by temperature and taste. These findings align with another study by Osman et al [2], which revealed patient dissatisfaction with the taste of hospital food. According to the staff, it is because salt usage can be little to none and sometimes not used, depending on the prescribed diet.…”
Section: Introductionsupporting
confidence: 92%
“…The interviews also assisted to build and improve the answer options. Details on the thematic analysis of the interview session for the process of item development can be gleaned from a previous study (22). Next, the questionnaire underwent a peer-reviewed process to identify any overlapping and duplication questionnaire.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…Hospital food service is of the utmost importance in food provision to more than 75% of hospital patients (Andersson et al 2013). Food consumption during hospitalization is determined by the quality of food and beverages which might have an impact on patients' recovery (Norshariza et al 2019;Osman et al 2022). Additionally, it is the responsibility of a hospital's food and nutrition service to provide adequate diets to patients and the meal provided must supply sufficient nutrients that can maintain or restore nutritional status during acute or chronic disease state (Gomes et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…An increment of malnutrition prevalence has been recorded among geriatric patients at 61.7% using Subjective Global Assessment (SGA) as the nutritional assessment tool (Abd Aziz et al 2018). Negative consequences associated with malnutrition include high mortality rates, increased hospital stays, and lower discharge rates (Osman et al 2022). The nutritional status of patients is assessed using Nutritional Risk Screening (NRS 2002) by recommendations made by European Society for Clinical Nutrition and Metabolism (ESPEN) for hospitalized patients (Kondrup et al 2003).…”
Section: Introductionmentioning
confidence: 99%